Choroid plexus in developmental and evolutionary perspective - Bill, Brent Roy; Korzh, Vladimir (Frontiers in Neuroscience, 2014)
The blood-cerebrospinal fluid boundary is present at the level of epithelial cells of the choroid plexus. As one of the sources of the cerebrospinal fluid, the choroid plexus plays an important role during brain development and function. Its formation has been studied largely in mammalian species. Lately, progress in other model animals, in particular the zebrafish, has brought a deeper understanding of choroid plexus formation, due in part to the ability to observe choroid plexus development in vivo. At the same time, advances in comparative genomics began providing information, which opens a possibility to understand further the molecular mechanisms involved in evolution of the choroid plexus and the blood-cerebrospinal fluid boundary formation. Hence this review focuses on analysis of the choroid plexus from developmental and evolutionary perspectives.